BRINGING COMMUNITIES AND THE UNIVERSITY TOGETHER: APPLIED ANTHROPOLOGY AT CALIFORNIA STATE UNIVERSITY, LONG BEACH. Issue 1 (May 2013) - LeMaster, Barbara; Quintiliani, Karen; Hunt, Allison; Bennett, Linda A.; Whiteford, Linda M.
<x xml:space="preserve">Abstract</x> California State University, Long Beach Applied Anthropology M.A. program actively engages in synergistic collaborations through applied faculty research, student MA projects, faculty–student collaborations, and classroom‐community partnerships. We highlight some of these collaborations and make suggestions for the sustainability of applied work in the academy.